FAKTOR-FAKTOR PENYEBAB RAMPAN KARIES PADA SISWA TK PERTIWI JEMBUNGAN I KABUPATEN BOYOLALI - Sadimin Sadimin; Tri Wiyatini; Hermien Nugraheni; Bedjo Santoso (Jurnal Kesehatan Gigi, 2017)
TITLEThe etiology of rampant caries in pre-school children in TK Pertiwi Jembungan I BoyolaliABSTRACTBaby bottle caries is a dental disease that begins from a tooth and concerns the multi-surface and spreads rapidly to other teeth due to persistent exposure to factors of cause. This study aims to determine the factors that cause rampan caries in students TK Pertiwi Jembungan I Boyolali District.The type of this research is quantitative descriptive with case study research method. The data were collected by examination of caries trajectory, saliva pH and PHP-M index, and questionnaires for time and questionnaire variables based on Bloom's approach theory covering environmental factors, behavior, health service and heredity. Priority problem using odd ratio data analysis test result obtained that the most dominant cause factor is practice (OR value = 16,25), attitude (OR value = 15,00) and knowledge (OR value = 9,3).The results showed that salivary pH value of all respondents was acid (pH 7.0) and 57% of respondents had bad category plaque index value. Time factor showed 57% of respondents were bad category. 48% of respondents who have knowledge of bad category. 61% of respondents already have a good attitude. 100% of respondents did not brush their teeth before bedtime. 83% of respondents have a habit of brushing their teeth only when bathing. Health care factors, 100% of respondents have never treated dental cavities and have not received dental health education, 52% of respondents have fragile teeth and 26% of respondents have a dental structure of crowding. Keywords : Caries rampan, kindergarten students